2012
DOI: 10.1002/hipo.22079
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic coding of dorsal hippocampal neurons between tasks that differ in structure and memory demand

Abstract: Hippocampal place fields show remapping between environments that contain sufficiently different contextual features, a phenomenon that may reflect a mechanism for episodic memory formation. Previous studies have shown that place fields remap to changes in the configuration of visual landmarks in an environment. Other experiments have demonstrated that remapping can occur with experience, even when the visual features of an environment remain stable. A special case of remapping may be trajectory coding, the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 54 publications
(83 reference statements)
1
30
0
Order By: Relevance
“…The most robust demonstrations of trajectory coding have been seen in continuous spatial alternation (Wood et al, 2000; Lee et al, 2006) and serial reversal tasks (Ferbinteanu and Shapiro, 2003). Interestingly, some tasks that are known to depend on the hippocampus, such as delayed spatial alternation do not elicit robust trajectory coding (Ainge et al, 2007a; Griffin et al, 2012; Hallock and Griffin, 2013). This set of findings argues against the interpretation of trajectory coding being a memory signal used in task performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most robust demonstrations of trajectory coding have been seen in continuous spatial alternation (Wood et al, 2000; Lee et al, 2006) and serial reversal tasks (Ferbinteanu and Shapiro, 2003). Interestingly, some tasks that are known to depend on the hippocampus, such as delayed spatial alternation do not elicit robust trajectory coding (Ainge et al, 2007a; Griffin et al, 2012; Hallock and Griffin, 2013). This set of findings argues against the interpretation of trajectory coding being a memory signal used in task performance.…”
Section: Resultsmentioning
confidence: 99%
“…Ainge et al (2012) compared prospective coding across behaviorally identical tasks and showed no differences in the coding behavior of hippocampal neurons between the memory-guided and cue-guided conditions. Conversely, a recent study showed that a large percentage of hippocampal neurons remapped between continuous alternation and conditional discrimination tasks, a phenomenon that was termed “task remapping” (See Figure 1; Hallock and Griffin, 2013). When a delay was added to the alternation task, however, there was very little remapping between tasks, suggesting that the temporal structure of the task (discrete vs. continuous trials) was driving the place cell remapping rather than the memory demand of the task (Hallock and Griffin, 2013).…”
Section: Place Cell Remappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Place cell maps were observed in both strategies but the cells participating and their firing patterns in the same maze were unrelated (Eschencko & Mizumori, 2007); similar remapping has been observed in animals switching between response and object choice strategies (Lee & Kim 2010) and between objects or positions of the same objects within an environment (Muzzio et al, 2009). Remapping has also been observed in a T-maze delayed non-matching to place task where distinct firing patterns were observed between sample trials, where the animal must encode its path, and choice trials, where the animal must remember the correct path (Griffin et al, 2007; also see Hallock and Griffin, 2013). In yet another task, remapping was observed when rats switched between start and goal arms while performing the same spatial memory task in the same maze (Bahar et al, 2011).…”
Section: What Is the “Memory Code” In The Hippocampus?mentioning
confidence: 95%